Cecum microbiota composition, fermentation characteristics, and immunometabolic biomarkers of Yunshang black goat fed varying dietary energy and protein levels - Binlong Fu; Xiaoqi Zhao; Muhammad Khan; Yanting Jiang; Weijuan Li; Maida Mushtaq; Baiji Danzeng; Xiaojun Ni; Zobia Azeem; Qingyong Shao; Bai Xue; Yina Ouyang (Frontiers in Microbiology)
IntroductionRuminants including goats have diverse microcosms of microbiota involved in diet digestion, absorption, and assimilation. Moreover, it is well known that changes in dietary regimens including nutrient levels result in varied gut microbiota composition, and ultimately, the performance and health of these animals.MethodsThe current study examined the effects of varying dietary energy and protein levels on the cecal fermentation, immune biomarkers, and microbiota characteristics of 80 male Yunshan Black Goats (6 months, ~35.82 ± 2.79 kg), divided into four diets: 1) High Energy-High Protein (HEHP), 2) High Energy-Low Protein (HELP), 3) Low Energy-High Protein (LEHP), and 4) Low Energy-Low Protein (LELP). Twenty goats (five from each treatment group) were randomly slaughtered after a 50-day feeding trial, and cecal digesta and tissue were sampled for microbial analysis.ResultsThe cecal content revealed that the high-energy groups (HEHP, HELP) had lower pH levels than the LEHP group (p < 0.05) and significantly higher valeric and isovaleric acid concentrations in HEHP. Although species richness (Chao1 index) remained consistent, the HEHP group showed higher diversity (Shannon and Simpson indices) than LEHP (p < 0.05). Dominant phyla included Bacteroidetes and Firmicutes; LEHP and LELP had significantly higher Bacteroidetes abundance than HELP, while HELP had higher Firmicutes abundance than LEHP (p < 0.05). Verrucomicrobia abundance was lower in LEHP than in HELP and LELP (p < 0.05). At the genus level, 311 genera were identified, with Clostridium, Prevotella, unidentified_BS11, and others showing significant variation. The HELP group had lower unidentified_BS11 than LEHP and LELP, and higher unidentified_Ruminococcaceae, Clostridium, and Lachnospiraceae than LEHP (p < 0.05). VFA metabolism, absorption, cytokine expression, and tight junction protein mRNA in cecal tissue were also analyzed. Genes like MCT-1 and SLC16A4, linked to VFA absorption, positively correlated with Paludibacter, which was associated with immune markers (TLR-3, TLR-4, IFN-γ) and Occludin expression. In contrast, VFA-related genes and tight junction proteins negatively correlated with unidentified Fibrobacterales, suggesting a microbial role in adaptive immunity.ConclusionThis study demonstrated that dietary energy and protein levels significantly influenced cecal fermentation, immune biomarkers, and microbiota composition in Yunshan Black Goats.